Modification of Polyurethane from Cardanol Biomass of Cashew Nut Shell with Ag Nanoparticles and Its Antibacterial Activity - Magdalena Devi Suryono; Muhammad Ilham Khairuddiin; Fauziyah Azhari; Maulidan Firdaus; Sentot Budi Rahardjo; Witri Wahyu Lestari (Jurnal Kimia Sains dan Aplikasi, 2026)
The cardanol-based polyurethane was systematically investigated for its chemical structure, thermal stability, surface hydrophobicity, morphology, dispersion of silver nanoparticles (AgNPs), crystalline features, and antibacterial performance. In this study, a Biobased polyurethane (PU) derived from cardanol extracted from cashew nut shell liquid (CNSL) was modified with silver nanoparticles (AgNPs) to develop antibacterial composite materials. Cardanol was isolated via liquid–liquid extraction and further purified using column chromatography. Fourier Transform Infrared (FTIR) spectroscopy and High-Performance Liquid Chromatography (HPLC) confirmed the successful removal of anacardic acid and the presence of cardanol. The cardanol-based polyol was synthesized via a thiol–ene click reaction and subsequently polymerized with 1,4-butanediol and hexamethylene diisocyanate to produce an elastomeric PU. AgNPs were incorporated at various loadings to evaluate their influence on physicochemical properties and antibacterial activity. FTIR analysis verified urethane bond formation, while thermogravimetric and differential thermal analysis (TG/DTA) demonstrated thermal stability up to 200°C. X-ray Diffraction (XRD) confirmed the face-centered cubic (FCC) crystalline structure of silver within the PU matrix. Field-emission scanning electron microscopy-energy dispersive X-ray (FESEM-EDX) revealed that PU containing 15 wt% AgNPs exhibited the most homogeneous nanoparticle dispersion. An increase in AgNPs content led to enhanced surface hydrophobicity and antibacterial performance. Antibacterial essays showed PU/AgNPs composites effectively inhibited Escherichia coli and Staphylococcus aureus, with the largest inhibition zones observed for PU/Ag containing 15 wt% AgNPs (16.40 mm and 12.60 mm, respectively). Overall, the results indicated that AgNP loading governs a trade-off between dispersion uniformity and antibacterial efficacy, with intermediate loading favoring homogeneous morphology and higher loading maximizing antibacterial performance. These findings highlight the potential of PU/AgNPs composites for use as antibacterial coating materials.